2014
DOI: 10.1093/heapol/czu072
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with task shifting of antiretroviral services in Ethiopia: implications for universal health coverage

Abstract: Formalized task shifting structures have been used to rapidly scale up antiretroviral service delivery to underserved populations in several countries, and may be a promising mechanism for accomplishing universal health coverage. However, studies evaluating the quality of service delivery through task shifting have largely ignored the patient perspective, focusing on health outcomes and acceptability to health care providers and regulatory bodies, despite studies worldwide that have shown the significance of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…This suggests that task-shifting has assisted in expanding access and maintaining HATCS without compromising quality and satisfaction with services. This has also been confirmed by other studies [ 60 , 61 ]. However, the quality of care was affected when HATCS were provided by untrained staff, increasing the chances of malpractice and changes in treatment plans.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that task-shifting has assisted in expanding access and maintaining HATCS without compromising quality and satisfaction with services. This has also been confirmed by other studies [ 60 , 61 ]. However, the quality of care was affected when HATCS were provided by untrained staff, increasing the chances of malpractice and changes in treatment plans.…”
Section: Discussionsupporting
confidence: 91%
“…High scores in the interpersonal manner construct showed that the patients were satisfied with the professional manner and empathy of the healthcare providers. Satisfaction in these two constructs might explain the correspondingly good levels of general satisfaction reported by the PLHIV clients [16]. Technical quality was perceived by the routine ART service group to be significantly better than that reported by the patients in the task-shifted service group (Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…Existing literature shows that patient satisfaction was an important indicator in evaluating healthcare service delivery or intervention [14]. Researchers in the United States, Vietnam, Ethiopia, and India reported the impact of task-shifted ART service, applying patient satisfaction as the study outcome [13,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…interventions in countries such as Nepal [82,90], Ugunda [117,118] Rwanda [75], Tanzania [50,77], Ethiopia [119], Afghanistan [62] and…”
Section: Discussionmentioning
confidence: 99%